Both-Bone Forearm Shaft Fractures Treated with Compression Plate Fixation in Adults - Henri Vasara, MD; Antti Stenroos, MD, PhD; Samuli Aspinen, MD, PhD; Jussi Kosola, MD, PhD; Turkka Anttila, MD; Panu H. Nordback, MD, PhD (JBJS Open Access)
Background:. Both-bone forearm shaft fractures (BBFFs) in adults carry a significant risk of adverse events (AEs). Based on the current literature, there is considerable variance in AE incidence reporting. We aimed to systematically review the literature on BBFFs in adults treated with compression plate fixation, assessing AEs and long-term outcomes. Methods:. We performed a systematic review based on the PubMed database on the current literature on adult BBFFs treated with open reduction and internal fixation with compression plates. Two authors independently collected the data, and a third author resolved disagreements between the 2 reviewers. The primary outcome measure was postoperative AEs, whereas the secondary outcome was to review the long-term outcomes. We evaluated the methodological quality of the studies with a modified version of the Coleman Methodology Score. Results:. Fifteen studies (12 retrospective case series and 3 randomized controlled trials) met the set inclusion criteria. In total, there were 944 patients, of whom 24% (n = 224) experienced some AEs, and 14% had major AEs requiring secondary operations or remaining persistent. The most common AEs were postoperative nerve injuries (incidence 7%, n = 64/944) and fracture nonunion (incidence 5%, n = 45/944). Disabilities of the Arm, Shoulder, and Hand scores were available for 135 patients (5 studies), with a mean score of 12.5 (range 0-61). According to the modified Coleman Methodology Scores, there were 2 good-, 1 fair-, and 12 poor-quality studies among the included studies. Conclusion:. BBFF compression plate fixation in adults poses a relatively high AE risk (24%). According to available patient-reported outcomes and range of motion measurements, the average postoperative outcomes are good, although a minor disability typically persists to some extent. There is a need for high-quality prospective trials assessing the treatment and outcomes of BBFFs in adults to improve forearm fracture treatment. Level of Evidence:. Level III. See Instructions for Authors for a complete description of levels of evidence.